2012
DOI: 10.1016/j.jacc.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Mortality as a Result of Direct Transport From the Field to a Receiving Center for Primary Percutaneous Coronary Intervention

Abstract: A STEMI system allowing EMS to transport patients directly to a primary PCI center was associated with a significant reduction in mortality. Our results support the concept of STEMI systems that include pre-hospital referral by EMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…6-8 Prehospital ECGs reduce the time from first medical contact to device activation, or “balloon” time (FMC2B), which is the first attempt to mechanically open the culprit lesion and restore blood flow. 9-13 However, the relative influence of the patient's distance from the PCI center on FMC2B time is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…6-8 Prehospital ECGs reduce the time from first medical contact to device activation, or “balloon” time (FMC2B), which is the first attempt to mechanically open the culprit lesion and restore blood flow. 9-13 However, the relative influence of the patient's distance from the PCI center on FMC2B time is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The University of Ottawa Heart Institute regional STEMI program serves a population of approximately 1.3 million residents in eastern Ontario, receiving patients from 17 referral hospitals as well as direct transport by paramedics from the field [13][15]. The current study was a prospective observational cohort study performed on consecutive eligible patients referred for PPCI between June 2012 and November 2012.…”
Section: Methodsmentioning
confidence: 99%
“…In the past year, evidence has emerged that direct transport of STEMI patients to a more distant PCI capable center (rather than to a nearer non-PCI center) leads to shorter overall reperfusion times and increased adherence to standard guidelines [5]. Additionally, retrospective analysis data comparing the two triage strategies has suggested that mortality may also be considerably reduced with direct transfer to a PCI center, bypassing the non-PCI center [6]. In a French registry, significant reductions in mortality were noted between 1995 and 2010, largely attributed to reductions in time from symptom onset to first medical contact, greater use of reperfusion therapy, and guideline recommended pharmacotherapy [7].…”
Section: Improved Systems Of Care For Stemimentioning
confidence: 99%